2000
DOI: 10.1001/archinte.160.3.293
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Spiral Volumetric Computed Tomography in the Diagnosis of Pulmonary Embolism

Abstract: To evaluate the evidence for the use of spiral volumetric computed tomography (SVCT) in the diagnosis of acute pulmonary embolism (PE), the 11 English-language studies published through July 1998 that compared SVCT with a reference standard for PE were systematically reviewed. Among the reviewed studies, methodological problems were common. Only 5 of these studies fulfilled 5 of 11 basic standards addressing important issues in diagnostic test research. The reported sensitivities of SVCT compared with pulmonar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
87
0
5

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(95 citation statements)
references
References 18 publications
3
87
0
5
Order By: Relevance
“…Initial studies of CTPA supported this appearance of diagnostic certainty, reporting sen-sitivity and specificity of greater than 90%, 3,4 but several subsequent studies have failed to reproduce these results. [5][6][7] Newer multidetector CT scans are believed to be more accurate than earlier singledetector CT, 8 but true estimates of CTPA test characteristics will not be known until publication of the forthcoming PIOPED II study. 9 Even without these data, CT-based diagnostic algorithms have already appeared.…”
Section: S Piral Computed Tomographic Pulmonary Angiography (Ctpa)mentioning
confidence: 99%
“…Initial studies of CTPA supported this appearance of diagnostic certainty, reporting sen-sitivity and specificity of greater than 90%, 3,4 but several subsequent studies have failed to reproduce these results. [5][6][7] Newer multidetector CT scans are believed to be more accurate than earlier singledetector CT, 8 but true estimates of CTPA test characteristics will not be known until publication of the forthcoming PIOPED II study. 9 Even without these data, CT-based diagnostic algorithms have already appeared.…”
Section: S Piral Computed Tomographic Pulmonary Angiography (Ctpa)mentioning
confidence: 99%
“…PE can mimic a vast number of cardiopulmonary diseases, particularly in elderly patients in whom it remains a diagnostic challenge. Contemporary diagnosis of PE rests on sequential diagnostic strategies usually including clinical probability, D-dimer test, compression ultrasonography (US) of the lower limbs, ventilation-perfusion lung scan or helical computed tomography (CT) and angiography [4][5][6].…”
mentioning
confidence: 99%
“…Potassium homeostasis is partly regulated by kidney and controlled by renin-angiotensin-aldosterone system. Urinary potassium excretion is a function of potassium concentration in the lumen of the cortical collecting duct (CCD) times the urine flow rate [6]. Determining the transtubular potassium concentration gradient (TTKG) is a novel clinical approach to estimate the urinary potassium excretion.…”
mentioning
confidence: 99%
“…Previous studies have shown that PE has been frequently overlooked, and therefore, the mortality rate in such cases is significantly increased (3,4) . One of the most important diagnostic methods in suspected cases of PE is computed tomography (CT) scans of the pulmonary artery (5,6) …”
Section: Introductionmentioning
confidence: 99%